132 GERIATRIC REHABILITATION IN THE COVID-19 ERA: SERVICE INNOVATION AND PATIENT OUTCOMES. (18th November 2021) - Flood, E; Browne, L; Kurian, S; Lynch, C; Doyle, M; Jordan, A; Varghese, R; Mello, S
Abstract: Background: The COVID-19 pandemic fundamentally changed the way rehabilitation services are delivered, with focus placed on individual in-room therapy and cessation of group sessions. Sparks Innovation and National Lottery funding was obtained to implement the 'In-Room Rehabilitation and Well-being Initiative'. This provided patients with individual physiotherapy equipment to use in their room thus maximizing time spent active during periods of isolation. We aim to describe service innovation occurring in a post-acute geriatric rehabilitation hospital during the COVID-19 era, and the resultant patient outcomes. Methods: Rehabilitation was provided to patients in-line with evidence-based practice and national infection prevention and control guidelines. Patients who were deemed appropriate by the multi-disciplinary team were provided with in-room therapy equipment. Prospective data was collected on service and patient outcomes. Functional outcome measurements were collected on admission and discharge and compared using a paired t-test. Results: Rehabilitation was provided to 260 patients, average age 80.5 years (range 63–98) with 46.5% male. The majority of patients were admitted with ortho-geriatric diagnoses or general deconditioning following illness (70%). The patients were complex with multiple medical, functional, and psychosocial care needs, as indicated by an average Rehabilitation Complexity Score of 11/20, with 100% of patients requiring daily therapy. Average length of stay (LOS) was 30.7 days (range 3–169), with 85% of patients discharged home. Performance in activities of daily living (Barthel Index: 62 vs 79, p < 0.0001), and mobility (Cumulative Ambulatory Score: 3.8 vs 5.3, p < 0.0001) significantly improved from admission to discharge. Conclusion: Despite ward closures, disruption to rehabilitation due to COVID-19 illness, and limitations on group therapies, our service achieved positive patient outcomes through innovation and delivery of high-quality evidence-based rehabilitation. Compared to the past eight years, 2020 had the lowest LOS and highest number of patients discharged home.